MILITARY-PATRIOTIC EDUCATION OF PRESCHOOL CHILDREN - Ellina E. A., Andrianova A. A. (University as a factor of Modernization of Russia: History and Prospects (to the 55th anniversary of the I.N. Ulyanov ChSU), 2024)
this article highlights the issues of patriotic education of preschoolers, which is aimed at the formation and development of a personality possessing the qualities of a citizen – patriot of the Motherland and capable of successfully fulfilling civic duties.
Keywords: патриотизм; нравственные чувства; Patriotism; нравственно-патриотическое воспитание; moral and patriotic education; moral feelings